2000
DOI: 10.1161/01.cir.102.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Chamber Pacing in the Treatment of Neurally Mediated Tilt-Positive Cardioinhibitory Syncope

Abstract: Background-This study was performed to compare implantation of a DDI pacemaker with rate hysteresis with no implant in respect to syncopal recurrences in patients with severe cardioinhibitory tilt-positive neurally mediated syncope. Methods and Results-Forty-two patients from 18 European centers were randomized to receive a DDI pacemaker programmed to 80 bpm with hysteresis of 45 bpm (19 patients) or no pacemaker (23 patients). Inclusion criteria were Ն3 syncopes over the last 2 years and a positive cardioinhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
2
14

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(141 citation statements)
references
References 20 publications
10
115
2
14
Order By: Relevance
“…En todos los estudios de estimulación cardiaca en pacientes vasovagales positivos a la basculación, se usó la estimulación cardiaca bicameral (con una función de respuesta en frecuencia que, ante una disminución rápida del ritmo cardiaco, el marcapasos instauraba estimulación cardiaca DDD rápida), pero no se comparó con la estimulación cardiaca bicameral convencional [20][21][22][23][24] .…”
Section: Selección Del Modo De Estimulación Cardiacaunclassified
See 2 more Smart Citations
“…En todos los estudios de estimulación cardiaca en pacientes vasovagales positivos a la basculación, se usó la estimulación cardiaca bicameral (con una función de respuesta en frecuencia que, ante una disminución rápida del ritmo cardiaco, el marcapasos instauraba estimulación cardiaca DDD rápida), pero no se comparó con la estimulación cardiaca bicameral convencional [20][21][22][23][24] .…”
Section: Selección Del Modo De Estimulación Cardiacaunclassified
“…La eficacia de la estimulación cardiaca se estudió en cinco ensayos clínicos multicéntricos aleatorizados [20][21][22][23][24] ; tres estudios sin enmascaramiento dieron resultados positivos y dos estudios con enmascaramiento dieron resultados negativos [21][22][23][24] . En los estudios aleatorizados y abiertos SYDIT y VASIS-PM 20,24 , se seleccionó a los pacientes por la respuesta cardioinhibitoria positiva (sobre todo asistólica) durante la prueba de basculación.…”
Section: Síncope Vasovagal Inducido Por Basculación (Recomendaciones unclassified
See 1 more Smart Citation
“…Two trials showed that patients with tilt-positive cardioinhibitory syncope benefited from pacing. 34,35 However, the control groups did not get a device and placebo effect could not be excluded. In a subsequent trial, patients with pacemakers were randomized to the device being "on" or "off", and pacing therapy did not reduce NCS incidence.…”
Section: Workup For Syncopementioning
confidence: 99%
“…In the late 1990s, reports were published of a decrease in rates of neurally mediated episodes of syncope by overdrive dual chamber pacing at 100 to 110 bpm, compared to non-paced patients with standard therapy. [27][28][29] However, in more recent trials, this was shown to be attributable to a placebo effect of pacemaker implants. 30,31) Thus, as in the case of drug therapy, the effectiveness of pacing for neurocardiogenic syncope has not been confirmed.…”
Section: Cardiac Pacingmentioning
confidence: 99%